Analyzing Destination Branding Themes Using Co-Word Analysis - Derviş, Hamid (IGI Global, 2024)
The chapter provides practical strategies for leveraging Social Network Analysis (SNA) in destination branding, offering insights on using interconnected keywords to create a cohesive brand identity extracted from Clarivate Analytics Web of Science (WOS). Using Istanbul, Konya, and Kastamonu showcased as destination brands, the chapter demonstrates how SNA can be applied in real-world contexts, providing insights into the benefits of a strategic branding approach through SNA. The author emphasizes the significance of a connected keyword network and offers practical strategies for leveraging these connections to establish a sustainable destination brand identity. The findings serve as a guide for tourism and hospitality practitioners, assisting them in creating compelling, sustainable destination brands. Similarly, this methodology can be applied to investigate the complex relationships among stakeholders, including local communities, businesses, government agencies, and tourists.